2022
DOI: 10.1038/s41598-022-15628-2
|View full text |Cite
|
Sign up to set email alerts
|

Inefficient Building Electrification Will Require Massive Buildout of Renewable Energy and Seasonal Energy Storage

Abstract: Building electrification is essential to many full-economy decarbonization pathways. However, current decarbonization modeling in the United States (U.S.) does not incorporate seasonal fluctuations in building energy demand, seasonal fluctuations in electricity demand of electrified buildings, or the ramifications of this extra demand for electricity generation. Here, we examine historical energy data in the U.S. to evaluate current seasonal fluctuation in total energy demand and management of seasonal fluctua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Even though TCI is not being adopted by the states that originally explored its implementation, this is an important dimension that states and regulators need to assess when developing transportation emissions reduction policies. The increased electricity needs that result from electrification transportation (Schnell et al 2019, Choma et al 2020, Waite and Modi 2020, and potentially buildings (Knobloch et al 2020, Buonocore et al 2022, are an important part of the full life cycle impacts of these policies. Including them in assessments and formally evaluating the effects of increased electricity demand is critical for detecting and preventing the inadvertent creation or exacerbations of areas with high air pollution around power plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though TCI is not being adopted by the states that originally explored its implementation, this is an important dimension that states and regulators need to assess when developing transportation emissions reduction policies. The increased electricity needs that result from electrification transportation (Schnell et al 2019, Choma et al 2020, Waite and Modi 2020, and potentially buildings (Knobloch et al 2020, Buonocore et al 2022, are an important part of the full life cycle impacts of these policies. Including them in assessments and formally evaluating the effects of increased electricity demand is critical for detecting and preventing the inadvertent creation or exacerbations of areas with high air pollution around power plants.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because vehicle electrification is a major strategy for reducing the emissions from transportation. Vehicle electrification will increase electrical generation; if this generation is not met with renewables, it will be met with fossil-fueled EGUs (Buonocore et al 2022). This could result in increased air pollution emissions, potentially eroding public health gains and producing new environmental justice (EJ) issues, or exacerbating old ones around existing EGUs.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the overall trend of higher cooling demand and lower heating demand, studies found substantial geographic and seasonal heterogeneities in demand changes (Hadley et al 2006, Mansur et al 2008, Apadula et al 2012, Cian et al, 2013, Buonocore et al 2022, Lyu et al 2022. These heterogeneities play an important role in various aspects of energy planning, such as fuel choice (Mansur et al 2008), equipment selection (E.I.A.…”
Section: Introductionmentioning
confidence: 99%
“…Conducting such an analysis is important for projecting source-specific energy changes (e.g. electricity for cooling vs. natural gas for heating), particularly in the context of building electrification (Buonocore et al 2022) and grid decarbonization (Abido et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of reducing green-house gas emissions from the building stock, the "Falcon curve" shows that relying solely on electrification will switch the electrical grid from summer to winter peaking and will require a massive increase in renewable energy production [1]. Therefore, to drive the decarbonization of the building sector and ensure grid stability, it is necessary to act on both envelope and systems in the renovation process.…”
Section: Introductionmentioning
confidence: 99%